A case study of culturally informed disability-inclusive education policy development in the Solomon Islands. Issue 5 (4th May 2017) - Carrington, Suzanne; Pillay, Hitendra; Tones, Megan; Nickerson, Julie; Duke, Jennifer; Esibaea, Benedict; Malefoasi, Ambrose; Fa'asala, Casper Joseph
ABSTRACT: Inclusive education in general, and disability-inclusive education in particular, is a high-level priority for development work in aid-supported countries. This paper presents a bottom-up process of developing disability-inclusive education policy in one country – the Solomon Islands. It is well understood that the promotion of quality in disability-inclusive education requires a clearly stated policy; however, in many developing countries, there has been a history of policy borrowing rather than culturally informed policy development. This paper will critically discuss how policy development occurs in aid-funded development work and then offers an alternative model of Australian aid-supported policy development as an in-depth case study.